Age at first birth and cardiovascular risk factors in the 1958 British birth cohort. Issue 7 (7th March 2017) - Lacey, Rebecca E; Kumari, Meena; Sacker, Amanda; McMunn, Anne
Abstract : Background: To assess relationships between age at first birth and cardiovascular risk factors in a large longitudinal study of men and women. By assessing associations for both genders, we were able to investigate biological versus social and behavioural explanations from early life through to adulthood. Methods: Multiply-imputed data on more than 7600 men and women of a British birth cohort study (National Child Development Study, 1958 British birth cohort) were used. Cardiovascular risk factors at age 44/45 years included body mass index, waist:hip ratio, blood pressure (systolic and diastolic), cholesterol (total, low and high-density lipoprotein), triglycerides, glycated haemoglobin, C reactive protein, von Willebrand factor and fibrinogen. Age at first birth was categorised as <20 years, 20–24 years, 25–29 years, 30–34 years or >34 years. Results: Being younger than 20 years of age at time of first birth was associated with an adverse cardiovascular profile by mid-life. Conversely, older parents had a lower cardiovascular risk as captured by lower body mass index, waist:hip ratio, blood pressure, high and low-density lipoprotein cholesterol, triglycerides, glycated haemoglobin, C reactive protein and fibrinogen. The relationship between age at first birth and cardiovascular risk factors was graded. Few differences between men and women were observed. Associations were largely unchanged after adjustment for early life factors but were partially mediated through adult social and behavioural factors. Conclusions: Age at first birth is inversely associated with differences in cardiovascular risk factors in mid-life in a large prospective birth cohort. Our results potentially suggest a social and behavioural rather than a biological explanation.